173k views
3 votes
Which of the following is equivalent to (c – 4)(c – 4)?

Which of the following is equivalent to (c – 4)(c – 4)?-example-1
User Joren
by
5.4k points

1 Answer

4 votes

For this case we must find an expression equivalent to
(c - 4) (c - 4), for this, we must apply distributive property, which by definition establishes:


(a + b) (c + d) = ac + ad + bc + bd

So:


(c - 4) (c - 4) = c ^ 2-4c-4c + (- 4) (- 4)

taking into account that
- * - = +


(c - 4) (c - 4) = c ^ 2-8c + 16

Answer:

Option C

User Sasith
by
6.1k points